Bengal politics : documents of the Raj, Vol. 1 (1936-39) - Rahim, Enayetur; Rahim, Joyce L. (University Press Limited, 1996)
Chiefly comprises fortnightly reports of the Governor of Bengal to the Viceroy and Governor-General of India and their replies, 1936 to 1947.